The effects of ultraviolet-B radiation on antioxidant status and survival in the zebrafish. - Charron, Richard Adrian. (University of Ottawa (Canada), 1999)
Increased exposure to solar radiation in the UV-B range (280-320 nm) is occurring globally at least partly due to anthropogenic degradation of stratospheric ozone. The direct impact of present ambient (1.95 W/m$\sp2$) and sub-ambient doses of UV-B radiation on muscle and skin tissue antioxidants in mature zebrafish (Brachydanio rerio) and on their hatching success and survival in early life stages was measured. Exposure of mature fish to sub-ambient doses of UV-B radiation both in the presence (1.28 W/m$\sp2$) and absence (1.72 W/m$\sp2$) of a cellulose acetate filter (blocks all wavelengths below 290 nm) resulted in a significant depression in muscle/skin total glutathione (TGSH) levels compared with controls and low UV-B treated fish. Exposure to an ambient intensity of UV-B resulted in a significant decrease in muscle/skin glutathione peroxidase (GPx) activity compared with controls and low treated fish. A coincident significant increase in catalase activity compared with controls and low UV-B treated fish was also observed. Changes in SOD, catalase, GPx and GSH status suggests a UV-B-mediated increase in cytosolic superoxide anion radicals (O$\sb2\sp-$) and hydrogen peroxide. Newly fertilized eggs exposed to ambient UV-B for the duration of the hatching period exhibited 1.68% hatching success. Newly hatched larvae were observed to be more sensitive to UV-B than the adults. (Abstract shortened by UMI.)
Keywords: Biology, Animal Physiology.